Menuju Masa Depan yang Lebih Baik: Membangun Kecerdasan Emosional dan Spiritual - Nesia Mu’asyara; Abdul Malik Syarif; Ahmad Syaputra; Ahmad Wafa Ahdillah; Donny Angga Kusuma; Muhamad Basar Riziq; Muhammad Ridho (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
Personal development in the context of modern life requires emotional intelligence (EQ) and spiritual intelligence (SQ) to face increasingly complex challenges. This research aims to explore the future principles oriented towards EQ and SQ and identify the role of both in improving the quality of life of individuals. The research uses a qualitative method with a descriptive approach, collecting data through in-depth interviews with individuals who are known to have high levels of EQ and SQ. The results of the study show that individuals with balanced EQ and SQ have high self-awareness, are able to build meaningful social relationships, and have a vision of life oriented towards spiritual values. The implications of this study suggest that the integration of EQ and SQ can help individuals face change more resiliently, make informed decisions, and achieve more holistic well-being. Findings.